The US unemployment insurance, a federal-state partnership: Relevance for reflections at the European level - Georg Fischer (Institute of Labor Economics (IZA), 2017)
This paper describes the US Unemployment Insurance (UI) in particular the federal-state partnership in governance, funding and policy making. It discusses 'national interest' as defined by the Federal authorities in relation to UI: income support, economic and employment stabilization and reemployment. The corresponding policy objectives might not be (fully) shared by the states and tensions and policy conflicts emerge. The paper assesses the capacity of the UI system to deliver on those nationwide defined objectives in particular during and after the Great Recession. The UI system had considerable anticyclical impact reinforced by federal intervention. The paper discusses the federal tools to influence state schemes and how they encourage the acceptance of national standards through conditional funding. During the great recession this proved to be temporarily successful for access to and duration of benefits. The often announced shift to more pro-active programs was seemingly more difficult to achieve. Recent policy proposals including those by the outgoing Obama Administration and by the Republican Speaker of the House, Paul Ryan, are reviewed. The paper concludes with reflections on the relevance of the US experience for European level unemployment benefit or welfare schemes. Given the strong position of the EU member states the US Federal-State partnership could be a more pertinent reference than the highly centralised UI systems in other federal states. The relation between federation wide standards and incentives for the reform of state systems, for sustainable financing and shifts to more pro-active policies might be of interest. Finally strengthening the anti-cyclical impact through federal intervention including funding mirrors debates on the role of automatic stabilisation mechanisms in the Euro Area.
Keywords: J65; J68; H75; 330; unemployment insurance; stabilization; adequacy; funding; federal-state partnership; USA; European Union